Economic viability of UK shale gas and potential impacts on the energy market up to 2030. (1st April 2018) - Cooper, Jasmin; Stamford, Laurence; Azapagic, Adisa
Highlights: UK shale gas is 2 times more expensive than LNG and 3 times more than US shale gas. Nevertheless, it is still more competitive than most other sources of electricity. Shale gas would have little effect on energy prices and consumer bills. The contribution to the GDP is small, an order of magnitude lower than in the US. The economic success of shale gas in the US may not be replicated in the UK. Abstract: The UK is in the early stages of developing a shale gas industry and to date six test wells have been drilled but none yet exploited commercially. Some argue that shale gas could reduce energy prices and improve national energy security. However, the costs of bringing commercial-size wells into operation are uncertain and the impact shale gas could have on the UK energy market is currently unknown. Therefore, this paper evaluates the economic viability of developing a UK shale gas industry and the impacts it could have on the UK gas and electricity markets and consumer energy bills up to 2030. The estimated life cycle (levelised) costs of shale gas production range from 0.47 to 56.74 pence/MJ (0.61–73 US cents/MJ), with an average value of 4.64 pence/MJ. The break-even price at which shale gas can be sold varies between 0.95 and 114.44 pence/MJ, averaging at 9.47 pence/MJ, depending on the volume of gas produced by a shale gas well. The latter is two times higher than imported liquefied natural gas, around 30% more expensive than UK natural gas and three times greater than the price of US shale gas. Electricity from shale gas is on average 17% more expensive than from domestic conventional gas but still more competitive than most other electricity options, including coal and renewables. However, the impact of shale gas on the energy market would be limited across the expected range of shale gas penetration into the gas and electricity mixes, suggesting that it would have little effect on energy prices. This is reflected in an almost negligible impact on consumer energy bills. The potential of shale gas to boost the UK economy is also limited, contributing 0.017–0.033% to the GDP. This is an order of magnitude lower than the contribution of US shale gas to its GDP (0.2%), indicating that the economic success of shale gas in the US may not be replicated in the UK. These findings will be of interest to shale gas developers and policy makers not only in the UK but in other countries considering exploitation of shale gas resources.